The effect of different doses of near infrared light on dopaminergic cell survival and gliosis in MPTP-treated mice. (2nd January 2016) - El Massri, Nabil; Johnstone, Daniel M.; Peoples, Cassandra L.; Moro, Cécile; Reinhart, Florian; Torres, Napoleon; Stone, Jonathan; Benabid, Alim-Louis; Mitrofanis, John
Abstract : We have used the MPTP (1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine) mouse model to explore whether (i) the neuroprotective effect of near infrared light (NIr) treatment in the SNc is dose-dependent and (ii) the relationship between tyrosine hydroxylase (TH)+ terminal density and glial cells in the caudate-putamen complex (CPu). Mice received MPTP injections (50 mg/kg) and 2 J/cm2 NIr dose with either 2 d or 7 d survival period. In another series, with a longer 14 d survival period, mice had a stronger MPTP regime (100 mg/kg) and either 2 J/cm2 or 4 J/cm2 NIr dose. Brains were processed for routine immunohistochemistry and cell counts were made using stereology. Our findings were that in the 2 d series, no change in SNc TH+ cell number was evident after any treatment. In the 7 d series however, MPTP insult resulted in ∼45% reduction in TH+ cell number; after NIr (2 J/cm2) treatment, many cells were protected from the toxic insult. In the 14 d series, MPTP induced a similar reduction in TH+ cell number. NIr mitigated the loss of TH+ cells, but only at the higher dose of 4 J/cm2; the lower dose of 2 J/cm2 had no neuroprotective effect in this series. The higher dose of NIr, unlike the lower dose, also mitigated the MPTP- induced increase in CPu astrocytes after 14 d; these changes were independent of TH+ terminal density, of which, did not vary across the different experimental groups. In summary, we showed that neuroprotection by NIr irradiation in MPTP-treated mice was dose-dependent; with increasing MPTP toxicity, higher doses of NIr were required to protect cells and reduce astrogliosis.